Implementation of an individually differentiated approach in training runners - Segal I.V. ,; Deryabina M.A. ,; Kiryakova O.S. ,; Nevyantseva Yu.S. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop and substantiate a model for the implementation of an individually differentiated approach in the training of highly qualified runners. Methods and structure of the study. Participants in the experiment were members of the national track and field team of 57 student-athletes. At the stages of the study, the following were carried out: questionnaire testing and analysis of the results shown at competitions, mathematical processing of the results obtained. Results and conclusions. The article reveals the features and patterns of training highly qualified runners. A model for implementing an individually differentiated approach in training runners is presented. External factors and individual characteristics that must be taken into account when selecting and differentiating tasks are identified.